Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, dan Pengungkapan CSR Pada Kinerja Keuangan Perusahaan - Hermayanti, Luh Gede Dian; Sukartha, I Made (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p03, 2019)
The purpose of this study is to prove empirically the effect of managerial ownership, institutional ownership, and disclosure of corporate social responsibility on the financial performance of mining companies listed on the Indonesia Stock Exchange for the period 2012-2016.. The data analysis technique used is multiple linear regression analysis. The results showed that the first and third hypotheses in the study were rejected, namely managerial ownership and disclosure of CSR did not affect the financial performance of mining companies listed on the Indonesia Stock Exchange for the period 2012-2016. The second hypothesis in this study is accepted, namely institutional ownership has a positive effect on the financial performance of mining companies listed on the Indonesia Stock Exchange for the period 2012-2016. Keywords : Institutional ownership, managerial ownership, disclosure of corporate social responsibility, financial performance